Music reduces pain and increases resting state fMRI BOLD signal amplitude in the left angular gyrus in fibromyalgia patients - Garza-Villarreal, Eduardo A.; Jiang, Zhiguo; Vuust, Peter; Alcauter, Sarael; Vase, Lene; Pasaye, Erick; Cavazos-Rodriguez, Roberto; Brattico, Elvira; Jensen, Troels S.; Barrios, Fernando A. (Frontiers in Psychology, 2015)
Music reduces pain in fibromyalgia (FM), a chronic pain disease, but the functional neural correlates of music-induced analgesia are still largely unknown. We recruited FM patients (n = 22) who listened to their preferred relaxing music and an auditory control (pink noise) for 5 minutes without external noise from fMRI image acquisition. Resting state fMRI was then acquired before and after the music and control conditions. A significant increase in the amplitude of low frequency fluctuations of the BOLD signal was evident in the left angular gyrus after listening to music, which in turn, correlated to the analgesia reports. The post-hoc seed-based functional connectivity analysis of the left angular gyrus showed found higher connectivity after listening to music with right dorsolateral prefrontal cortex, the left caudate, and decreased connectivity with right anterior cingulate cortex, right supplementary motor area, precuneus and right precentral gyrus. Pain intensity analgesia was correlated (r = .61) to the connectivity of the left angular gyrus with the right precentral gyrus. Our results show that music-induced analgesia in FM is related to top-down regulation of the pain modulatory network by the default-mode network.